2013
DOI: 10.1002/uog.11171
|View full text |Cite
|
Sign up to set email alerts
|

Rightward convexity of the great vessel arising from the anterior ventricle: a novel fetal marker for transposition of the great arteries

Abstract: Objectives

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 14 publications
1
14
0
Order By: Relevance
“…[56] In both cases, these signs were noted, but interestingly normal arrangement pattern of 3VV known as the “dash-dot-dot” also could be produced. In a normal 3VV, the arrangement of PA, aorta, and superior vena cava (SVC) is from left to right and anterior to posterior, with a “dash” pattern created by PA continuing into DA seen in long axis while aorta and SVC seen in cross section forming the “dot-dot” pattern [Figure 4a and b].…”
Section: Discussionmentioning
confidence: 99%
“…[56] In both cases, these signs were noted, but interestingly normal arrangement pattern of 3VV known as the “dash-dot-dot” also could be produced. In a normal 3VV, the arrangement of PA, aorta, and superior vena cava (SVC) is from left to right and anterior to posterior, with a “dash” pattern created by PA continuing into DA seen in long axis while aorta and SVC seen in cross section forming the “dot-dot” pattern [Figure 4a and b].…”
Section: Discussionmentioning
confidence: 99%
“…In 2013, Menahem et al [32] reviewed 21 fetuses whose prenatal diagnosis of TGA was confirmed postnatally. In all cases of TGA, the authors observed an abnormal right convexity of the vessel Fig.…”
Section: Prenatal Diagnosis Of Tga By Ultrasonography and Echocardiogmentioning
confidence: 99%
“…Tongsong et al (2010) [31] 5 16-39 (mean, 26) In this study, the authors observed there were only two vessels (aorta and superior vena cava) in all cases of TGA instead of three in the 3VV ("misnomer 3 vessels"). Menahem et al (2013) [32] 21 First and second trimesters…”
Section: Prenatal Diagnosis Of Tga By Ultrasonography and Echocardiogmentioning
confidence: 99%
“…As in this case of transposition of the great arteries (Figure ), the solitary vessel represents the aorta, which is typically positioned anterior and superior to the nonvisualized pulmonary artery. In this case, the aorta makes a characteristic rightward convex course from the anterior right ventricle to the descending aorta …”
Section: Anatomy and Techniquementioning
confidence: 99%